Management of the spastic hip in cerebral palsy. Issue 1 (February 2017) - Givon, Uri
Abstract : Purpose of review: Spastic hip dysplasia (SHD) is a common finding in patients with cerebral palsy, with a higher incidence in more involved patients, causing disability and reducing quality of life in these patients. SHD is the most serious orthopedic problem seen in cerebral palsy patients, and requires special attention and tenacious evaluation of the patients. The aim of this article is to review the new developments in the treatment of SHD. Recent findings: Patients with cerebral palsy were shown to have better hip joint morphology when they had access to hip surveillance programmes, with proactive search of patients with progressing hip subluxation and early intervention. Prediction of progression of SHD is now available based on the experience of these programmes. Patients who underwent hip joint reconstruction showed that incongruent joints remodeled following a Dega osteotomy. Patients who underwent a varus osteotomy of the femoral neck without pelvic reconstruction had a higher rate of recurrence when they were older and the SHD was more severe. Health-related quality of life measures improved following hip joint reconstructions and salvage procedures. Conclusion: Patients with cerebral palsy should be monitored with a well-defined hip surveillance programme, with early identification and timely intervention for SHD.